Bioinspired silk fibroin nano-delivery systems protect against 5-FU induced gastrointestinal mucositis in a mouse model and display antitumor effects on HT-29 colorectal cancer cells in vitro. Issue 7 (9th August 2021) - Hudita, A.; Radu, I. C.; Galateanu, B.; Ginghina, O.; Herman, H.; Balta, C.; Rosu, M.; Zaharia, C.; Costache, M.; Tanasa, E.; Velonia, K.; Tsatsakis, A.; et al.
Abstract: Colorectal cancer (CRC), is the second cause of cancer-related deaths worldwide is one of the most prevalent types of cancers. Conventional treatment continues to rely on surgery, chemotherapy, and radiotherapy, but for advanced cases, adjuvant chemotherapy remains the main approach for improving surgical outcomes and lower the disease recurrence probability. Chemotherapy-induced gastrointestinal (GI) toxicity is the main dose-limiting factor for many chemotherapeutic regimens, including 5-FU, and one of the biggest oncological challenges. Up to 40% of the patients receiving 5-FU get mucositis, 10–15% of which develop severe symptoms. In this context, our study aimed to develop a bioinspired nanosized drug delivery system as a strategy to reduce 5-FU associated side effects, such as GI mucositis. To this end, SF-based nanoparticles were prepared and characterized in terms of size and morphology, as well as in terms of in vitro antitumoral activity on a biomimetic colorectal cancer model by investigation of apoptosis, DNA fragmentation, and release of reactive oxygen species. Additionally, the capacity of the SF-based nanocarriers to offer intestinal protection against 5-FU-induced GI mucositis was evaluated in vivo using a mouse model that mimics the chemotherapy-associated gut mucositis occurring in colorectal cancer. Our studies show that silk fibroin nanoparticles efficiently deliver 5-FU to tumor cells in vitro while protecting against drug-induced GI mucositis in a mouse model.